The 1 Repetition Maximum Mechanics of a High-Handle Hexagonal Bar Deadlift Compared With a Conventional Deadlift as Measured by a Linear Position Transducer. Issue 1 (January 2018) - Lockie, Robert G.; Moreno, Matthew R.; Lazar, Adrina; Risso, Fabrice G.; Liu, Tricia M.; Stage, Alyssa A.; Birmingham-Babauta, Samantha A.; Torne, Ibett A.; Stokes, John J.; Giuliano, Dominic V.; Davis, DeShaun L.; Orjalo, Ashley J.; et al.
Abstract : Abstract: Lockie, RG, Moreno, MR, Lazar, A, Risso, FG, Liu, TM, Stage, AA, Birmingham-Babauta, SA, Torne, IA, Stokes, JJ, Giuliano, DV, Davis, DL, Orjalo, AJ, and Callaghan, SJ. The 1 repetition maximum mechanics of a high-handle hexagonal bar deadlift compared with a conventional deadlift as measured by a linear position transducer. J Strength Cond Res 32(1): 150–161, 2018—The high-handle hexagonal bar deadlift (HHBD), a variation of the conventional deadlift (CD), is said to reduce the lift range of motion, which may change the mechanics of the lift. However, no research has investigated this. This study compared the mechanics between a 1 repetition maximum (1RM) CD and HHBD. Thirty-one strength-trained subjects (21 men, 10 women) completed a 1RM CD and HHBD. A linear position transducer measured lift distance, duration, and work; and peak and mean power, velocity, and force. The presence of a sticking region (SR) was determined for each lift. A repeated-measures analysis of variance (ANOVA) calculated differences between 1RM CD and HHBD mechanics. A one-way ANOVA compared the mechanics of each lift between subjects who exhibited an SR or not, and the SR between the CD and HHBD. Significance was set at p < 0.01. Subjects lifted a greater load in the HHBD (154.50 ± 45.29 kg) compared with the CD (134.72 ± 40.63 kg). Lift distance and duration were 22 and 25% shorter during the 1RM HHBD, respectively. The HHBD featured greater peak power and velocity, and peak and mean force; more work was done in the CD. Most subjects did not exhibit a CD (68%) or HHBD (77%) SR. There were no differences in CD or HHBD mechanics between subjects with or without an SR, and no differences in SR region distance or duration between the CD and HHBD. Greater force can be generated in the HHBD, which could have implications for strength-training adaptations over time.